Simplysiti Sdn. Bhd. / Syarifah Salsabila Sayed Hassan - Sayed Hassan, Syarifah Salsabila (2021)
I have been given the responsibility by my lecturer to do an individual assignment which is case study to enlighten me more about the subject that I studied fundamental of entrepreneurship. The main purpose of doing this case study is to further develop a branch of thought in the field of entrepreneurship at the same time it can give me an idea to establish my own business and being a successful entrepreneur in the future. The company that I have chosen to do this case study is Simplysiti Cosmetic that owned by Dato’ Sri Siti Nurhaliza binti Tarudin which is a Malaysian singer. The reason why I choose her company is because this company has been run over ten years and still manage to maintain on top after came out with so many obstacles in competing with others cosmetic company. They always present with the new idea in making an innovation towards their product to make sure that It up to date with this generation.